Marketing Analysis Of Processed Wood Leftover Dua Putri Wooden Stand In Sidomulyo Village Oransbari Regency: in - Dhea Msen; Bambang Nurgoho; Dina Arung Padang (JURNAL KEHUTANAN PAPUASIA, 2024)
This study aims to determine the types of processed wood, the shape and size of processed wood waste, marketing strategies, and the utilization of processed wood waste produced by Stand Kayu Dua Putri in Sidomulyo Village. Based on the results of observations and interviews, it is known that Stand Kayu Dua Putri processes seven types of commercial wood, namely Matoa wood (Pometia pinnata), eucalyptus (Dargon wood), merbau wood (Intsia bijuga), milk wood (Alstonia beatricis), cempaka wood (Michelia champaca), king wood (Eucalyptus deglupta), and marsawa wood (Genus Anisoptera). The sawing process produces wood waste in the form of sawdust, poles, and sabetan which have various shapes and sizes, as well as different utilization potentials. In terms of marketing, wood waste is sold directly to end consumers, but there is a striking price difference between Stand Kayu Dua Putri and the Manokwari area. In Sidomulyo, sabetan is sold for IDR 600,000 per truck, while in Manokwari it is around IDR 50,000 per bundle. Sawdust is even given for free in Sidomulyo, but sold for IDR 300,000 per truck in Manokwari. The utilization of wood waste in Sidomulyo Village is carried out productively, such as for livestock fences and plant trellises, thus contributing to supporting agricultural and livestock activities and reducing wood waste that is thrown away.